2020
DOI: 10.1097/md.0000000000020322
|View full text |Cite
|
Sign up to set email alerts
|

Patient-perceived service needs and health care utilization in people with type 2 diabetes

Abstract: The aim of this study was to investigate service needs and health care utilization among people with type 2 diabetes, further to identify the relationship between service needs and health care utilization. We used a self-reported questionnaire to collect data regarding demographic and diabetes characteristics, service needs toward self-management and follow-up care, and 4 health care utilizations during past year. Multiple linear regression and binary logistic regression were used to test the impac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 53 publications
0
8
0
Order By: Relevance
“…This result is considerably lower than might be expected from the relative prevalence of antidepressant-prescribed individuals in men and women in the general population, which a large international study [27] reported as being almost double for women compared to men. This may suggest reduced gender inequalities in access to antidepressant treatment for men with comorbid depression and T2DM compared to those without diabetes, perhaps due to the increased contact with healthcare services for people with diabetes of both genders compared to those without diabetes [49] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This result is considerably lower than might be expected from the relative prevalence of antidepressant-prescribed individuals in men and women in the general population, which a large international study [27] reported as being almost double for women compared to men. This may suggest reduced gender inequalities in access to antidepressant treatment for men with comorbid depression and T2DM compared to those without diabetes, perhaps due to the increased contact with healthcare services for people with diabetes of both genders compared to those without diabetes [49] .…”
Section: Discussionmentioning
confidence: 99%
“…Higher odds of antidepressant prescribing may have been expected in insulin users compared to participants not using insulin, as a 2006 meta-analysis [52] showed that insulin use was associated with increased depression symptoms in T2DM. Insulin users represent participants with more complex T2DM, who may be more likely to have increased contact time with healthcare services [49] , which could provide increased opportunity to discuss antidepressant treatment. Again, however, this was not found to be the case.…”
Section: Discussionmentioning
confidence: 99%
“…However, many others do not go to health services, where they would have care with preventive measures for the low CVR they currently have. This means that there are areas of opportunity for effective primary care, focused on improving the care programs for patients with early diagnosis of CVR, with interventions to modify lifestyle and change to healthy behaviors as the most important step for both the health system and the patient, without forgetting that to achieve a change the perceived need should be taken into account, and the knowledge of adults concerning the importance of turning to health services for timely detection and care should be reinforced [31].…”
Section: Discussionmentioning
confidence: 99%
“…mixed research design uses both qualitative and quantitative approaches. The qualitative approach will be major and exploratory, and the quantitative methodology will be done in sequence [15].…”
Section: Methodsmentioning
confidence: 99%
“…The expected bene ts of using m-health should meet patients' needs and requirements. It should be implemented in a manner to support feedback loops in the self-management regime [15].…”
Section: Data Analysis Planmentioning
confidence: 99%